Compound Words In Suwawa Language - Tiara Suciani Kamaru; Fatmah AR. Umar; Salam (TRANSBAHASA, 2023)
This study examines compound words in the Suwawa language, which involve the combination of two words to create new meanings and are commonly used in Suwawa conversations. The research focuses on two key aspects: (1) the forms of compound words in Suwawa and (2) the meaning of compound words in Suwawa. Employing a qualitative descriptive method, the study aims to elucidate the forms and meanings of compound words in Suwawa. Data were collected from Suwawa language speakers residing in Tingkohubu Timur village, Suwawa Subdistrict, utilizing data collection tables and employing interview, documentation, listening, and recording techniques. The data analysis involved presenting, reducing, and verifying the data to draw comprehensive conclusions. The findings reveal two significant outcomes. Firstly, the Suwawa language exhibits three forms of compound words: substantive subordinative, attributive subordinative, and coordinative compound words. Secondly, compound words in Suwawa convey three distinct meanings: noun, verb, and adjective compound words. This research sheds light on the structure and semantic aspects of compound words in the Suwawa language, contributing to a deeper understanding of Suwawa linguistics.